Biodiesel Production from Grilled Chicken Oil Using Hexane as a Co-Solvent (Journal of Pharmaceutical Negative Results, 2022)
As a result of the high prices of traditional fuels and the pollution problems resulting from the use of this type of fuel, there was an urgent need to search for actual alternatives that directly contribute to reducing global dependence on traditional fuels and reducing the percentage of pollution. Therefore, biofuels are distinguished in solving part of these problems. This research dealt with fuel production Bio-fuel from grilled chicken oil waste innovatively, we have never found its use, so this research relied on the production of biofuel from grilled chicken oil waste using hexane as a co-solvent through the one-step exchange esterification process hexane is reused again through the distillation process. At a low temperature, it had a major role in increasing the yield, reducing the reaction time and reaction temperature, and reducing the ratio of ethanol used to the oil ratio, as well as improving the standard specifications of the resulting fuel. the fuel produced in this way is suitable for mixing with traditional fuels and for use.